Welfare Effect of Farmers’ Participation in Soil Conservation: Concept, Connotation and Evaluation Index Framework - Wang Min; Wei Jie; Tang Qiang; He Xiubin; Li Jinlin (Shuitu baochi tongbao)
[Objective] A concept, connotation and evaluation index framework of welfare effect of farmers’ participation in soil conservation practices was systematically reviewed, which could provide a scientifical basis for comprehensive evaluation of the welfare effect of soil conservation. [Methods] By assembling existing publications and relevant standard documents, the concept and connotation of welfare effect of soil conservation were formulated, and the logical relationship between soil conservation benefits and soil conservation welfare effect. Furthermore, the evaluation scale of the welfare effect of soil conservation was sorted out, and an evaluation index framework for the welfare effect was proposed. [Results] The welfare effect of soil conservation had intrinsic characteristics of clear evaluation objects, monetizable value, high correlation with participation degree, individual difference, and group consistency. It is also considered to be deepened and expanded understandings of the benefits of soil conservation, and this relationship is inter-contained and inter-included. Evaluation of the soil conservation welfare effect should be based on a comprehensive evaluation of soil conservation benefits, and its index framework should include multiple elements such as economic welfare, social welfare, and ecological welfare. [Conclusion] The welfare effect of farmers’ participation in soil and water conservation has not yet gained enough attention currently. The evaluation of the welfare effect of soil and water conservation only focuses on policy-based soil and water conservation projects, and its evaluation indicators and methods have not formed a unified understanding. It is necessary to further study the theory and methodology of the welfare effect of soil and water conservation, thereby providing references for decision-making in the construction of soil and water conservation in the new era.